Effects of Modeling on the Behavior of Prestressed Concrete System - Adjie, Akbar Putro; Hariandja, Binsar; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
This study deals with the modeling of prestressed concrete components and its effects on the behavior of the structure. Two cases are presented, i.e., simple vs continuous beams, and crossing of prestressed and reinforced concrete beams. Based on the findings in this study, the modeling has significant effects in prestressed concrete behavior. The effects might create serious problems on structural safety if not addressed properly in the analysis and design of prestressed concrete systems. As much as possible, it is best to design prestressed components as free-standing statically determinate systems, thereby avoiding the possibility of additional secondary stresses that may reduce the capacity of the designed member. To achieve the above goals, it is best to use a precast concrete system to build a prestressed concrete system.